PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA FISIKA BERBASIS MODEL MEMORIZATION LEARNING PADA MATERI LAPISAN BUMI UNTUK KELAS VII SMP - Pratama, Handoko Anas; Fakhruddin Z, Fakhruddin Z; Zulirfan, Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning tools developed are learning tools based on theMemorization Learning model for the earth layer material for class VII SMP / MTsn,consisting of RPP, LKPD, and Learning Outcomes Test. The purpose of this research isto produce learning tools based on a valid Memorization Learning model on the earthlayer material. This type of research is a Research and Development (R&D) with a 4Dmodel design. The research instrument used was the RPP validation assessment sheet,LKPD, and the Learning Outcomes Test which were used by the validator to assess thelearning tools. The data was collected by providing learning tools to the validator to bevalidated using the RPP validation sheet, LKPD and Learning Outcomes Test. Dataanalysis in this study used descriptive analysis, by calculating the validity score of eachindicator of the learning device. Based on the results of the validity data analysis, theaverage value of the validity of meeting lesson plans 1 was 3.25 with the high category,meeting lesson plans 2 was 3.26 with the high category, meeting lesson plans 3 was3.26, with the high category and meeting lesson plans 4 was 3.32 with high category.The average validity of LKPD 1 was 3,27 with high category and LKPD meeting 1 3,12with high category, LKPD meeting 2 3,15 with high category, LKPD meeting 3 3,12with high category, and LKPD meeting 4 3,28 with the high category. The averagevalidity of the Learning Outcomes Test is 3.00 in the high category, so that the overallaverage of learning tools is 3.17 in the high category. Thus the learning device basedon the Memorization Learning model is declared valid and suitable for use in earthlayer material for class VII SMP / MTsn.Key Words: Physics Learning Device, Memorization Learning Model, CognitiveSstudyResult Test,